Influence of In-stream Ecosystem Restoration Techniques on the Fish Ecology of the River Nabongo in Eastern Uganda - Remigio Turyahabwe; Muhamud Wambedde Nabalegwa; Joyfred Asaba; Andrew Mulabbi (Jurnal Perikanan Universitas Gadjah Mada, 2022)
The study was the first in Uganda to assess the responses of fish community assemblages to introduced woody debris structures in a tropical river in Eastern Uganda. For comparison purposes, two different woody debris structures (simple and complex) were introduced in river Nabongo, and their effect on fish assemblage and feeding was established based on experiments conducted in two heterogeneous stream environments (a pool and a riffle). Results showed that sampling plots treated with restoration structures registered higher fish species richness, diversity, and abundance than sampling plots without restoration structures (control plots) at each site. The study (experiment) applied a stratified sampling design which used purposive identification of a pool and a riffle in River Nabongo Catchment. Fish were captured using a drift net, an electro-fishing gear, and a hand net. Data were analysed using a one-way ANOVA generated from STATA version 14. At the pool site, total fish density varied significantly from plot to plot (P<0.05) but was highest in the complex structures with 64±1.08 fishes/m2 and lowest with 24±0.82 fishes/m2 in untreated plots. K-factor did not vary significantly in untreated plots at the pool site but significantly differed from treated plots at P<0.05. The relative abundance of fish species at the pool site was highest in the complex structures with 40.7±0.66% and 21.5±0.42% before structures but was least in the control plot, varying significantly from plot to plot at P<0.05. It was concluded that woody debris restoration is an effective stream restoration technique. Fish individuals, trophic groups, and taxa more densely colonised sampling plots that had structures than those that did not have structures.